2017
DOI: 10.2298/jmmb150911002l
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and structure evolution of the SiO2-MgO-FeO-CaO-Al2O3 slag in ferronickel smelting process from laterite

Abstract: The SiO 2 fractions in laterite-nickel ores are quite high, thus certain amount of lime should be used as fluxing material to achieve good fluidity and desulfurization capacity in industrial smelting process. However, this operation leads to an additional cost of lime. In addition, the increase of slag volume decreases the effective furnace volume. To avoid such problem, partial reduction of FeO has been suggested. Therefore, the high SiO 2 , low MgO and FeO and very little CaO slag is formed, which was less s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…[15]; it was confirmed by the FTIR results as well. The same result was reported by other investigators [6]. However, when experimental temperature was below 1598 K, the viscosity increased significantly with the increase of FeO X /SiO 2 .…”
Section: Effect Of Zno/pbo On Slag Viscositysupporting
confidence: 91%
See 1 more Smart Citation
“…[15]; it was confirmed by the FTIR results as well. The same result was reported by other investigators [6]. However, when experimental temperature was below 1598 K, the viscosity increased significantly with the increase of FeO X /SiO 2 .…”
Section: Effect Of Zno/pbo On Slag Viscositysupporting
confidence: 91%
“…Battle and Hager [5] found that the addition of SiO 2 increased the viscosity of lead smelting slag, while the additions of ZnO decreased the viscosity at high temperatures, but raised the slag liquidus temperature. Lv et al [6] investigated the effect of FeO content on the viscosity and structure in the SiO 2 -MgO-FeO-CaO-Al 2 O 3 slag system. The results showed that the viscosity decreased and the mass fraction of the suspended particles increased with the increase of FeO content.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the viscosity of laterite smelting slags, the readers are referred to the paper which was published by X.M. Lv et al [19]. The authors of the present work thought that use of colemanite could be a solution to decrease physical losses.…”
Section: Introductionmentioning
confidence: 80%
“…A previous study on calcium additives in garnierite was conducted, but the valuable metals in the minerals could not be comprehensively utilized [26][27][28][29][30][31]. The purpose of this work is to explore a new process and provide a highly efficient and energy saving method, named the vacuum carbothermal reduction-magnetic separation method, to comprehensively utilize the garnierite.…”
Section: Introductionmentioning
confidence: 99%